Tick‐borne infectious diseases in Australia. Issue 7 (17th April 2017) - Graves, Stephen R; Stenos, John
Summary: Tick bites in Australia can lead to a variety of illnesses in patients. These include infection, allergies, paralysis, autoimmune disease, post‐infection fatigue and Australian multisystem disorder. Rickettsial (Rickettsia spp.) infections (Queensland tick typhus, Flinders Island spotted fever and Australian spotted fever) and Q fever (Coxiella burnetii) are the only systemic bacterial infections that are known to be transmitted by tick bites in Australia. Three species of local ticks transmit bacterial infection following a tick bite: ► the paralysis tick (Ixodes holocyclus) is endemic on the east coast of Australia and causes Queensland tick typhus due to R. australis and Q fever due to C. burnetii; ► the ornate kangaroo tick (Amblyomma triguttatum) occurs throughout much of northern, central and western Australia and causes Q fever; and ► the southern reptile tick (Bothriocroton hydrosauri) is found mainly in south‐eastern Australia and causes Flinders Island spotted fever due to R. honei. Much about Australian ticks and the medical outcomes following tick bites remains unknown. Further research is required to increase understanding of these areas.